2019
DOI: 10.3389/fimmu.2019.00475
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglanin-E2 Potentiates the Suppressive Functions of Human Mononuclear Myeloid-Derived Suppressor Cells and Increases Their Capacity to Expand IL-10-Producing Regulatory T Cell Subsets

Abstract: Myeloid-derived suppressor cells (MDSC) emerged as major factors driving the tumor progression due to numerous immunosuppressive mechanisms they possess. Prostaglandin (PG)E2 is shown critical for the induction of MDSC and their suppressive functions in vivo, but it is poorly understood how it affects the capacity of MDSC to induce different subsets of regulatory T cells (Treg). By using a novel protocol for the generation of mononuclear (M)-MDSC, we showed that PGE2 potentiates the GM-CSF/IL-6-dependent induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 85 publications
3
58
0
Order By: Relevance
“…Samples were scored on a 0-4 extent scale (0 = normal; 1 = <5%; 2 = 6-30%, 3 = 31-60%, 4 = >60%) for the fraction of the lung affected in any manner (Extent 1) and for the fraction of the lung affected in the worst manner (Extent 2). Samples were scored on a 0-4 scale (0 = none; 1 = few (<5 in focus); 2 = mild numbers (5-10); 3 = moderate numbers (11)(12)(13)(14)(15)(16)(17)(18)(19)(20); 4 = marked numbers (>20)) for numbers of mixed granulomas (ill-formed granulomas with a mixture of macrophages and lymphocytes), defined granulomas (well-defined with separation of macrophages, epithelioid, or multinucleated giant cells with lymphoid aggregates), perivascular lymphoid aggregates, peribronchiolar lymphoid aggregates, histocytes (macrophages), foamy macrophages, neutrophils, cholesterol clefts, and acid-fast bacteria. Scoring was performed by a pathologist who was blinded to the experimental condition of each sample.…”
Section: Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were scored on a 0-4 extent scale (0 = normal; 1 = <5%; 2 = 6-30%, 3 = 31-60%, 4 = >60%) for the fraction of the lung affected in any manner (Extent 1) and for the fraction of the lung affected in the worst manner (Extent 2). Samples were scored on a 0-4 scale (0 = none; 1 = few (<5 in focus); 2 = mild numbers (5-10); 3 = moderate numbers (11)(12)(13)(14)(15)(16)(17)(18)(19)(20); 4 = marked numbers (>20)) for numbers of mixed granulomas (ill-formed granulomas with a mixture of macrophages and lymphocytes), defined granulomas (well-defined with separation of macrophages, epithelioid, or multinucleated giant cells with lymphoid aggregates), perivascular lymphoid aggregates, peribronchiolar lymphoid aggregates, histocytes (macrophages), foamy macrophages, neutrophils, cholesterol clefts, and acid-fast bacteria. Scoring was performed by a pathologist who was blinded to the experimental condition of each sample.…”
Section: Histologymentioning
confidence: 99%
“…For example, protection against aerosol challenge with Mtb conferred by intravenous BCG vaccination was linked to epigenetic reprogramming of bone marrow derived macrophages in mice [19]. Additionally, BCG vaccination was able to prevent immune pathology and bacterial dissemination independently of CD4 T cells in a mouse model of TB reactivation [20].…”
Section: Introductionmentioning
confidence: 99%
“…In order to analyse the effect of L. brevis BGZLS10-17 supernatant on polyclonal proliferation of MLNC, the cells were labeled with carboxyfluorescein succinimidyl ester (CFSE, 1 µM, Thermo Fisher Scientific, Waltham, MA, USA) according to manufacturer's protocol, and then treated with Concanavalin A (2.5ug/ml, Sigma) either in the presence or absence of L. brevis BGZLS10-17 supernatants. The proliferation of CFSE-labeled MLNC was analyzed within live cells, as determined by simultaneous staining with propidium iodide (PI, Sigma, 10ug/ml) after the cultures, by flow cytometry according to Tomić et al 66 . The percentage of proliferation was calculated using the proliferation fit statistics in FCS Express 4 software (De Novo Software, Glendale, CA, USA).…”
Section: Measurement Of Proliferation Of Mesenteric Lymph Node Cellsmentioning
confidence: 99%
“…PTGS2, also known Cox2, is an enzyme responsible for the synthesis of prostanoids. Studies have shown that PTGER2 has potential in producing anti-inflammatory cytokines including IL-10 in vivo ( Okla et al., 2019 , Tomić et al., 2019 ). IL-10/Cox2/PTGER2 could be influenced by Mycobacterium avium infection in dendritic cells and by Antrodia cinnamomea fermented product in chicken cells ( Kim et al., 2019 , Lee et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%